GENETIC RELATEDNESS OF ESBL AND NON-ESBL SALMONELLA TYPHIMURUM ISOLATED FROM POULTRY BIRDS AND POULTRY HANDLERS IN NASARAWA STATE, NIGERIA - Ibrahim, T.; Ngwai, Y. B.; Ishaleku, D.; Tsaku, P. A.; Nkene, I. H.; Abimiku, R. H. (FUDMA JOURNAL OF SCIENCES, 2020)
Multidrug resistant salmonellosis infection is an important global public health problem particularly in sub-Saharan Africa, where it commonly manifests as gastroenteritis and/or bloodstream infections in both children and adults. Salmonella Typhimurium has a broad-host-range and poultry birds are an important reservoir. The unrestricted use of Beta-lactams has generated resistance through a gene encoded Extended Spectrum Beta-lactamase (ESBL) enzyme production, which impedes the successful therapy of infections. This study aims at investigating the genetic relatedness of ESBL and non-ESBL S. Typhimurium strains isolated from humans and Poultry birds. A total of 19 S. Typhimurium isolated from Poultry (droppings, flesh, feeds) and handlers (feces, hand swabs) in a previous study were used. These had earlier been identified using pre-enrichment and selective enrichment culture media. Further identification was carried out using conventional biochemical screening tests and slide serology tests using polyvalent antisera. Antibiotic susceptibility testing including the Double Disk Synergy test (DDST) for screening of ESBL production was carried out as described by the Clinical and Laboratory Standards Institute (CLSI) guidelines. This study also employed the PCR-RFLP method which involves the simple restriction digestion of purified 16S rRNA of Salmonella and variation in the banding patterns revealed their genetic relatedness. All the strains were found to share identical molecular base profiles hence are genetically related variants. The selective pressure due to antibiotic mismanagement in Poultry farming is the likely trigger of ESBL production observed to occur only among the S. Typhimurium strains from poultry origin. This calls for a holistic approach in